A quality framework for personalised residential supports for adults with developmental disabilities - Cocks, Errol; Boaden, Ross (Wiley-Blackwell Publishing Ltd, 2011)
Background. The Personalised Residential Supports (PRS) Project provided detailed information about the nature, purposes and outcomes of PRS from the perspectives of key stakeholder groups including people with developmental disabilities, family members and service providers. Although these forms of support have developed over the past two decades, there is a dearth of empirical work that has explored the characteristics of PRS. In contrast, there is a multitude of empirical studies on congregate forms of residential support with a clear trend towards study of the characteristics of relatively small, congregate residential settings.Methods. Personalised Residential Supports was conceived initially in the study as having four key criteria in the support arrangements – a high degree of: individualisation; individual/family influence; informal relationships; and, person-centredness. Four methods of data collection were used to develop a descriptive framework for PRS: a review of empirical and descriptive literature that met inclusion criteria; case studies carried out over 2 years of six adults whose living arrangements met the initial PRS criteria; a focus group of adults with developmental disabilities; and, a series of written surveys of 18 people who were ‘experts’ in their experience and knowledge of PRS-type support arrangements. The latter group included family members, service providers and policymakers. Each dataset was analysed separately and independently by the authors and a third researcher, followed by a process of conciliation and consensus in which the quality framework was developed. Two iterations of the expert group surveys were used to fine tune the framework.Results. Qualitative analysis resulted in a PRS quality framework made up of nine themes containing 28 attributes. Descriptions of each theme and attribute are provided. The nine themes were named as: Assumptions, Leadership, My Home, One Person at a Time, Planning, Control, Support, Thriving and Social Inclusion. Conclusion. This study identified the characteristics of PRS as reported by key stakeholder groups. On face value, the themes expressed in the PRS framework have relevance to all forms of supported accommodation, for many different groups of people. The research is continuing by further development of the framework that will enable its use in the evaluation of existing or planned residential support arrangements.